Description of Physical Discomfort in Elderly - Rina Anggraeni; Kitri Aristantini; Novi Indrayati; Riani Pradara Jati (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Physical discomfort can occur in the elderly due to degenerative processes. Physical discomfort that is often found in the elderly is chronic pain in physical ailments. The research objective was to identify physical discomfort in the elderly in Balok Village, Kendal District, Kendal Regency. The research design used was a descriptive survey. The sample in this study amounted to 52 respondents with a total sampling technique. The measuring instrument is a questionnaire. Data analysis using univariate. The results of univariate analysis of physical discomfort in the Balok Village, Kendal District, found that 29 respondents (55.8%) experienced physical discomfort and 23 respondents (44.2%) did not experience physical discomfort. Physical problems due to degenerative processes cause physical discomfort in the elderly. Most of the elderly (55%) experience physical discomfort due to the aging process in elderly in Balok Village Kendal District Kendal Regensy.